Data on Librarians’ Perceptions of Participation in a Citizen Science Project in a Network of Public Libraries - Pimentel, Filipa Alexandra Santos; Esteves Gomes, Liliana Isabel (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2024)
Citizen Science (CS) is an approach to scientific work and part of the Open Science movement. This study aims to analyse the perception of the librarians about their participation in the aBEIRAr project, which is a CS partnership for the valorisation of the territory developed in the Intermunicipal Network of Libraries of Beiras and Serra da Estrela (RIBBSE) in Portugal. The methodology comprised a literature review, and the case study includes an interview and a survey. Of the results obtained, the following stand out: the libraries are the driving forces behind the aBEIRAr project; they choose the themes, organise and dynamize the activities in their local communities, and establish various partnerships with the mediation of the project's scientific coordination; the level of satisfaction of the librarians in this project is very satisfactory; in the libraries, after carrying out the aBEIRAr project, the number of participants in other face-to-face activities and the interaction on their social network profiles increased; librarians consider that CS can bring to public libraries and their users participative scientific knowledge. The data provides valuable insights into the possibilities and challenges associated with executing CS projects in collaboration with public libraries. These findings contribute to the ongoing discussion about the role of libraries as essential community centers.